Sustainable Sound Insulation Panel From Used Textile - MOHD AZRI, MUHAMMAD NABIL; WAN ALI, WAN MUHAMMAD ALIMIE; DARUS, MUHAMMAD NUR LUQMAN; MOHAMMAD, HAIRUDDIN (Multidisciplinary Applied Research and Innovation, 2026)
Textile waste and noise pollution are two urgent problems that affect human health and environmental sustainability. By employing recovered textile waste, such as cotton, polyester, and blended materials, to create Sustainable Sound Insulation Panels (S-SIP), this study suggests a green breakthrough. Building affordable panels that lessen noise pollution and solid textile waste is the goal. Choosing appropriate textile waste, creating sandwich and multilayer panel architectures, and utilizing impedance tube techniques to measure acoustic performance are all part of the methodology. The findings show notable sound absorption performance that is on par with conventional acoustic materials, especially in the mid-to-high frequency regions. This study supports the circular economy and sustainability goals, which are in line with SDG Goals 11, 12, and 13.